Analisis model pembelajaran contextual teaching and learning (ctl): penerapan, kelebihan, serta kelemahannya dalam pembelajaran pai - Zahro, Salsabila Raudhatuz (Maliki Interdisciplinary Journal, 2025)
This research discusses the application of the Contextual Teaching and Learning (CTL) model in Islamic Education (PAI), highlighting its implementation, advantages, and disadvantages. CTL is an approach that emphasizes the connection between learning materials and real-life experiences, so that students not only understand concepts theoretically but also can relate them to everyday life. In the context of PAI, CTL plays an important role in forming a deeper understanding of Islamic values and encouraging students to internalize religious teachings in real practice, such as worship, morals, and transactions. The analysis results show that CTL has advantages, among others, increasing learning motivation, training critical thinking skills, strengthening cooperation, and making learning more meaningful. However, CTL also has weaknesses, such as requiring more time, demanding a more intensive role from teachers, and the potential for a less conducive classroom atmosphere if not managed well. Therefore, CTL can be an effective alternative strategy for Islamic Education teachers, provided that its implementation is accompanied by optimal planning and classroom management.